The Use of Teams Games Tournament Learning Model through Wordwall Media to Improve Learning Outcomes of Pancasila Education - Gunawan, Jelita Vita; Dianasari, Dianasari; Nurkholis , Nurkholis (FKIP - Universitas Riau, 2025)
This classroom action research was motivated by the low learning outcomes of class VC students at the UPTD of SD Negeri 1 Weru Lor in the Pancasila Education subject, especially in Chapter 4